2020
DOI: 10.3390/ijerph17072172
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Drinking Water Quality at the Point of Collection and within Household Storage Containers in the Hilly Rural Areas of Mid and Far-Western Nepal

Abstract: Accurate assessments of drinking water quality, household hygenic practices, and the mindset of the consumers are critical for developing effective water intervention strategies. This paper presents a microbial quality assessment of 512 samples from household water storage containers and 167 samples from points of collection (POC) in remote rural communities in the hilly area of western Nepal. We found that 81% of the stored drinking water samples (mean log10 of all samples = 1.16 colony-forming units (CFU)/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Our BBN models (1B and 2B) showed that the water quality at POCs critically affected the water quality at the POU in the study area, which has also been found by others 6 , 42 . We also found that types of water source used by the households determine the drinking water quality that they have at home, similar to the findings in rural Honduras 43 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Our BBN models (1B and 2B) showed that the water quality at POCs critically affected the water quality at the POU in the study area, which has also been found by others 6 , 42 . We also found that types of water source used by the households determine the drinking water quality that they have at home, similar to the findings in rural Honduras 43 .…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, we were able the analyse the water quality at POU by considering not only the water management and hygiene situation at home, but also the broader scope, such as the situation at the water source. Moreover, the conventional statistical analysis methods, e.g., bivariate correlation or regression analyses, often quantify the effect of the individual variable on water quality, but not a combination of variables or pathways 6 , 10 , 16 . The BBN approach was able to simulate both the effects in one model and can then help to prioritise the interventions that improve the water quality at household level, i.e., either targeting one variable or combination of multiple variables.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we observed that animals were often kept in or near the home and brought indoors overnight. Such practices have been shown to increase exposure to faecal contamination in the household environment in other rural settings [15,[57][58][59]. Other studies conducted in India and Bangladesh highlighted the importance of faecal contamination of animal origin in the domestic environment, including source and stored drinking water, hands, and soil [43,44].…”
Section: Diarrhoeamentioning
confidence: 99%